Rozwój kompetencji językowo-komunikacyjnej ucznia języka angielskiego w ekosystemie szkolnym. Obserwacje poszerzone o doświadczenia w nauczaniu podczas pandemii Covid-19 w 2020 roku - Filar-Pieczkowska, Judyta (Scripta Neophilologica Posnaniensia, 2022)
Pandemic Covid-19 was the time which undermined the existing systems of work and communication in all fields including education. Firstly the model of linguistic-communicative competence was defined in ecolinguistic perspective. Secondly the author aimed to verify if development of student’s linguistic-communicative competence in school ecosystem was shattered in pandemic environment and if it did so in what way. It was assumed that a teacher in order to shape student’s resources of skills, knowledge and motivation uses verbal and non-verbal managing strategies at certain levels: managing strategies of knowledge, managing strategies of interaction resources and managing strategies of class infrastructure.